Important prognostic factors for the long-term survival in non-small cell lung cancer patients treated with combination of chemotherapy and conformal radiotherapy - Crvenkova, Simonida; Pesevska, Meri (My University, 2015)
Combined modality therapy is standard of care for patients with unresectable locally advanced non-small cell lung cancer (NSCLC), however, insufficient data exist regarding prognostic factors in this disease setting.